Development of Chobmons Prototype: Cholesterol and Blood Sugar Level Monitoring System Based on Internet of Things (IoT) using Blynk Application: Heni Sumarti, Tria Nurmar’atin, Hamdan Hadi Kusuma, Istikomah Istikomah, Irman Said Prastyo - Heni Sumarti Heni Sumarti; Tria Nurmar’atin Tria Nurmar’atin; Hamdan Hadi Kusuma Hamdan Hadi Kusuma; Istikomah Istikomah; Irman Said Prastyo Irman Said Prastyo (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2022)
In the era of the industrial revolution 4.0, we need remote technology and products that d not created new medical waste piles. An unhealthy lifestyle can cause many diseases, either degenerative diseases, namely over rate cholesterol and blood sugar level. High cholesterol and blood sugar levels are causes of major influence on atherosclerosis, stroke, micro-vascular, and cardiovascular complications. We offer a non-invasive cholesterol and blood sugar monitoring device based on red LED and infrared light absorption using the Nellcor DS-100A sensor. This technology can help reduce cumulative medical waste and help health workers to monitor patients remotely. This study used ten random samples to calibrate cholesterol and blood sugar levels. The coefficient of determination values were 0.9580 and 0.9581, respectively, which gave excellent values so that the study is continued by collecting data. Data retrieval use 20 random sample data to measure cholesterol and blood sugar levels, the average accuracy prototype is 90.26% and 91.16%, respectively. It shows great potential in determining estimation value at cholesterol and blood sugar levels. The monitoring system can show the data on the LCD display in Blynk Application with the average time required of 1.07 s.